A new method for contact characteristic analysis of the tapered roller bearing in wind turbine main shaft. (November 2022) - Jiang, Zhiyuan; Huang, Xianzhen; Zhu, Huibin; Jiang, Rui; Du, Shanshan
Highlights: A novel 5DOF-HHO model with bearing clearance and preload is proposed. The meta-heuristic optimization is adopted to solve vector displacement. The accuracy and efficiency of the 5DOF-HHO are verified by three models. The coupling effects of clearance and preload on contact characteristic and fatigue life are investigated. Abstract: Premature failures of TRB in wind turbine remain a significant contributor to high operation and maintenance costs. The analysis of contact characteristics is the premise of the TRB failure investigation. In this paper, a novel five degrees of freedom (5DOF) TRB model which considers bearing clearance and preload, is established. Instead of the Newton-Raphson method, the meta-heuristic optimization is adopted to solve the nonlinear system by the L2 -norm minimization control. This improvement can intelligently judge the load region of TRB, avoid the selection of initial values and improve the convergence speed. The load distribution results are compared to the simulation results of the finite element model, Romax model and Harris model to verify the effectiveness of the proposed model. Besides, the proposed method has a higher efficiency than the existing methods. Finally, the influences of bearing clearance and preload on the contact characteristic and fatigue life are discussed.